(untitled) (Research, Society and Development, 2022)
Water is an essential natural resource for all forms of life in the world. Its availability is a management agent today for not to be lacking in the future and sustaining all ecosystems. Monitoring the water quality is mandatory to ensure the effectiveness of its various uses. In recent years, mathematical simulation models for water quality are common in scientific research. Thus, the objective is to analyze the mathematical models that appear most frequently in the literature and their main characteristics. Mathematical modeling allows predicting the behavior of a given system, that is, the reservoir, being possible to estimate its evolution over time. As this study was classified as an exploratory research, it collaborated in the line of investigation and encouraged operational research to analyze reservoir systems, such as residential pools, in terms of water quality.